Antioxidant-Rich Extracts of Terminalia ferdinandiana Interfere with Estimation of Cell Viability - Saleha Akter; Rama Addepalli; Michael E. Netzel; Ujang Tinggi; Mary T. Fletcher; Yasmina Sultanbawa; Simone A. Osborne (MDPI AG, 2019)
The impact of plant extracts and phytochemicals on in vitro cell viability is usually assessed by employing cell viability assays dependent upon the activity of dehydrogenase enzymes. The CellTiter 96® AQueous One Solution Cell Proliferation Assay (CellTiter) was used to measure cell viability in response to antioxidant-rich extracts of Terminalia ferdinandiana fruits. Conflicting results were obtained from this assay whereby higher concentrations of extracts significantly increased cell viability compared to lower concentrations. Intrinsic reductive potential was observed in a cell-free system when extracts were added directly to the CellTiter assay reagent. To confirm this effect in a similar cell proliferation assay, we employed the CellTiter-Blue® Cell Viability Assay and again observed increased viability with increased concentrations of the extracts and direct reduction of the assay reagent by the extracts in cell-free systems. In the search for a cell proliferation assay that would not be directly affected by the plant extracts, we identified the CyQUANT® NF Cell Proliferation Assay that is based on the estimation of DNA content in viable cells. Cell viability decreased with increasing concentrations of the extracts. Accordingly, the results of the present study indicated that cell viability assays reliant upon dehydrogenase activity may lead to false positive results when testing antioxidant-rich plant extracts with intrinsic reductive potential, and alternative cell viability assays should be used to measure the cell viability.